2020
DOI: 10.3389/fmed.2020.00269
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Multi-Omics Study on the Gut Microbiota in Critically Ill Patients After Cardiovascular Surgery Combined With Cardiopulmonary Bypass With or Without Sepsis (MUL-GM-CSCPB Study): A Prospective Study Protocol

Abstract: Introduction: Fever of unknown origin (FUO) and hemodynamic instability are complications that develop after cardiac surgery combined with cardiopulmonary bypass (CPB) for heart disease. Patients who develop fever with hemodynamic instability after cardiac surgery may have systemic inflammatory response syndrome or sepsis. Cardiopulmonary bypass (CPB) is a technique that temporarily takes over the function of the heart and lungs during cardiac surgery. Recent reports suggest that early bloodstream infections o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…From a microbiological point of view, a large number of infections observed were due to pathogens included in the family of Enterobacteriaceae . This can be explained by considering that intestinal ischaemia reperfusion that occurs during cardiac surgery and in end-stage cardiovascular diseases will induce a systemic inflammatory reaction and may cause intestinal flora translocation [ 20 ]. Interestingly, among Enterobacteriaceae isolated in our cohort, 40.7% were carbapenem-resistant.…”
Section: Discussionmentioning
confidence: 99%
“…From a microbiological point of view, a large number of infections observed were due to pathogens included in the family of Enterobacteriaceae . This can be explained by considering that intestinal ischaemia reperfusion that occurs during cardiac surgery and in end-stage cardiovascular diseases will induce a systemic inflammatory reaction and may cause intestinal flora translocation [ 20 ]. Interestingly, among Enterobacteriaceae isolated in our cohort, 40.7% were carbapenem-resistant.…”
Section: Discussionmentioning
confidence: 99%
“…As we have identified in the present study, the early predictors for long-term mortality should provide evidence for risk stratification and early intervention, such as the implementation of physical, psychological and nutritional support, among critically ill surgical patients during and after the ICU admission [ 28 ]. Furthermore, the culture positivity may potentially reflect the alternation of microbiota, and accumulating evidence have shown the crucial role of microbiota among critically ill patients in the past decade [ 8 , 27 ]. Freedberg et al .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence have shown the crucial role of chronic critical illness (CCI), characterised by persistent organ dysfunction, vulnerability for secondary infection, prolonged ICU course and high resource utilisation after discharge, among critically ill surgical patients [ 7 ]. A number of studies have demonstrated the critical illness-associated prolonged microbial alternation among critically ill surgical patients [ 8 10 ]. One recent study further characterised CCI with the prolonged immunological and metabolic alternation in 144 critically ill surgical patients with abdominal infection [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal microbiome is important in regulating health and homeostasis [15][16][17][18], and its dysregulation (termed intestinal dysbiosis) has been well studied in critical illness [19][20][21] and the cardiac surgical population [22][23][24]. With dysbiosis, an imbalance in the normal microflora of the gut occurs.…”
Section: Introductionmentioning
confidence: 99%